2016
DOI: 10.1021/acsami.5b09831
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing and Moldable Metallogels as the Recyclable Materials for Selective Dye Adsorption and Separation

Abstract: Four multiresponsive and self-sustaining metallogels were synthesized by the reaction of the disodium salt of the ligand carboxymethyl-(3,5-di-tert-butyl-2-hydroxy-benzyl)amino acetic acid with Cd(II) and Zn(II) halides, which were found to show excellent selectivity for dye adsorption and separation, and one of the gels shows a rare self-healing property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 54 publications
(65 reference statements)
2
90
0
Order By: Relevance
“…They employed Cd(II) and Zn(II) complexes of carboxymethyl-(3,5-di-tertbutyl-2-hydroxybenzyl)amino acetic acid. 61 They demonstrated that selective uptake of cationic dyes such as methylene blue and crystal violet could be achieved from mixtures with anionic dyes such as methyl orange or fluorescein. The best uptake levels of 56 mg g À1 for crystal violet were relatively modest, but a key advantage of this system was that the gels had high mechanical strength, and exhibited self-healing properties.…”
Section: Fig 12mentioning
confidence: 99%
“…They employed Cd(II) and Zn(II) complexes of carboxymethyl-(3,5-di-tertbutyl-2-hydroxybenzyl)amino acetic acid. 61 They demonstrated that selective uptake of cationic dyes such as methylene blue and crystal violet could be achieved from mixtures with anionic dyes such as methyl orange or fluorescein. The best uptake levels of 56 mg g À1 for crystal violet were relatively modest, but a key advantage of this system was that the gels had high mechanical strength, and exhibited self-healing properties.…”
Section: Fig 12mentioning
confidence: 99%
“…In recent years, metal–organic gels (MOGs) have attracted a great deal of attention due to their potential application in sensing, molecular recognition, catalysis, drug delivery, and dye adsorption, Low molecular weight MOGs are formed due to various non‐covalent interactions which are responsible for the rapid self‐assembly process of the discrete metal complexes and formation of the microstructures where a significant amount of solvent molecules are entrapped inside the network. These weak non‐covalent interactions, as well as the microstructure, can be easily deformed through the external stimuli, and material can undergo the gel to sol transition or vice‐versa.…”
Section: Introductionmentioning
confidence: 99%
“…Although various materials such as clay and modified clay (Li et al 2018), graphene-based nanocomposites (Zhu et al 2014, organosilica nanoparticles , orderly porous carbon (Peng et al 2014, Chen et al 2016, carbon nanotubes (Machado et al 2016), metallogels (Karan and Bhattacharjee (2016)), metal-organic frameworks (Li et al 2015b, Zhao et al 2015, Jia et al 2016, and cellulose materials (Annadurai et al 2002) have been used for the adsorption of organic pollutants and heavy metal ions, their low adsorption capacities, adsorption rates, selectivities, or complex preparation processes restricted their wide application. Activated carbon is the most effective and widely used adsorbent because of its porous structure, high specific surface area, high adsorption capacity, and several functional groups, which allow the safe and fast removal of dyes without any preliminary treatment (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%